Analisis Kinerja Inspektorat Dalam Melakukan Pengawasan Di Sekretariat Jenderal DPD RI - Ninuk Arifiyani; Dini Gandini Purbaningrum (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The DPD RI Inspectorate is tasked with overseeing the implementation of government affairs. However, there are several problems in the DPD RI Inspectorate such as the limited number of auditors, suboptimal budget, and low transparency in managing audit reports. The purpose of this study is to analyze the performance of the Inspectorate in the supervisory function at the General Secretariat of DPD RI. The research method used is descriptive with qualitative analysis. Data was collected through interviews, documentation, and observation. This research uses Agus Dwiyanto's theory (2006: 50) as follows: 1) Productivity, 2) Service quality, 3) Responsiveness, 4) Responsibility, 5) Accountability. The results showed that the performance of the Inspectorate was quite good in general, although not optimal due to constraints such as insufficient human resources and insufficient budget. The suggestion of this research is to increase the number of human resources and conduct socialization about applications that can be used by the Inspectorate..